DELETERIOUS ORAL HABITS: RELATIONSHIP WITH THE Z-SCORE BOBY MASS INDEX AND ANXIETY IN CHILDREN - Dellazzana, Amanda Alves; Berlese, Denise Bolzan; Haeffner, Leris Salete Bonfanti; Pascotini, Fernanda dos Santos (Revista Conhecimento Online: Diversidade e Inclusão Social, 2017)
Evaluate the relationship between the presence of deleterious oral habits, the Z-score of BMI and anxiety in scholars. Analytical cross-sectional study of 64 children from a Municipal Public School in the city of Santa Maria-RS from May to November 2013. It was verified anthropometry and applied a deleterious oral habit's questionnaire, for assessment of anxiety was used the The Revised Childrens Manifest Anxiety Scale (RCMAS). Data were analyzed in Stata10, was calculated the median and used Wilcoxon test, considering as significant p<0.05. Results: 59.4 % of the students were female, the BMI Z-score median was higher in boys and the RCMAS median score was higher in girls (p<0.05). The presence of the habit of biting objects and mouth/tongue/cheek were the ones which showed higher scores on the anxiety scale (p<0.05). The anxiety score was similar in relation to the nutritional status of the children. It was conclude that the Z-score of BMI is not associated with the presence of deleterious oral habits, but girls and students who have at least one deleterious oral habit and mainly the habit of biting objects and corner of the mouth/tongue/cheek have higher scores for anxiety. Keywords: Habits. Body Mass Index. Anxiety. Children. RESUMO Avaliar a relação entre a presença de hábitos orais deletérios, pontuação Z-score do IMC e ansiedade em crianças em idade escolar. Estudo transversal analítico com 64 crianças de uma Escola Pública Municipal de Santa Maria-RS no período de maio a novembro de 2013. Foi verificada antropometria e aplicado questionário sobre hábitos orais deletérios, para avaliação de ansiedade aplicou-se Escala "O que penso e sinto" (OQPS). Os dados foram analisados em Stata10, foi calculada mediana e utilizado teste de Wilcoxon, considerando como significante p <0,05. Resultados: 59,4% dos alunos eram do sexo feminino, a mediana do Z-score do IMC foi maior nos meninos e o Z-score médio do OQPS foi maior nas meninas (p <0,05). A presença dos hábitos de morder objetos e boca / língua / bochecha foram os que apresentaram maiores escores na escala de ansiedade (p <0,05). O escore de ansiedade foi semelhante em relação ao estado nutricional das crianças. Concluiu-se que o Z-score do IMC não está associado à presença de hábitos orais deletérios, mas meninas e estudantes que têm pelo menos um hábito oral deletério e principalmente o hábito de morder objetos e canto da boca / língua / bochecha têm escores mais altos para a ansiedade. Palavras-chave: Hábitos. Índice de massa corporal. Ansiedade. Crianças.